Towards the development of a North Australia social justice strategy : final report - Australia. North Australia Social Justice Strategy Task Force; Australia. Department of Housing and Regional Development; Australia. Office of Northern Development (Darwin : Office of Northern Development : Dept. of Housing and Regional Development, 1994)
Report highlights the impediments to effective delivery of government services and the policy changes required to improve service delivery at the community level; service issues and strategies; includes a section on Indigenous issues over and above the main reporting.
"March 1994"
Keywords: Social justice; Government policy - State and territory - Western Australia; Health services; Government policy - Commonwealth; Social welfare; Politics and Government - Social justice; Community development; Government policy - State and territory - Northern Territory; Government policy - State and territory - Queensland; Economics - Economic development; Australia, Northern -- Social conditions; Western Australia (WA); Northern Territory (NT); Australia